2005
DOI: 10.1002/gcc.20268
|View full text |Cite
|
Sign up to set email alerts
|

Microarray‐based CGH of sporadic and syndrome‐related pheochromocytomas using a 0.1–0.2 Mb bacterial artificial chromosome array spanning chromosome arm 1p

Abstract: Pheochromocytomas (PCC) are relatively rare neuroendocrine tumors, mainly of the adrenal medulla. They arise sporadically or occur secondary to inherited cancer syndromes, such as multiple endocrine neoplasia type II (MEN2), von Hippel-Lindau disease (VHL), or neurofibromatosis type I (NF1). Loss of 1p is the most frequently encountered genetic alteration, especially in MEN2-related and sporadic PCC. Previous studies have revealed three regions of common somatic loss on chromosome arm 1p, using chromosome-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 52 publications
1
27
1
Order By: Relevance
“…Moreover, most PCC in our study (22/36) had loss of the entire short arm of chromosome 1, by contrast to our previous study, where we found regional 1p loss in half of the cases (Aarts et al 2006). We speculate that the observed difference with our own previous studies and with series from others is related to the composition of the study group, which in the only present study comprised sporadic cases.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Moreover, most PCC in our study (22/36) had loss of the entire short arm of chromosome 1, by contrast to our previous study, where we found regional 1p loss in half of the cases (Aarts et al 2006). We speculate that the observed difference with our own previous studies and with series from others is related to the composition of the study group, which in the only present study comprised sporadic cases.…”
Section: Discussioncontrasting
confidence: 99%
“…We speculate that the observed difference with our own previous studies and with series from others is related to the composition of the study group, which in the only present study comprised sporadic cases. In the few cases with partial loss, no minimal region of common loss could be determined, preventing us to speculate on the presence of one region harboring tumor suppressor genes on 1p, which have been postulated by various authors (Geli et al 2005, Aarts et al 2006. Still, based on the high frequency of 1p loss in PCC, we support the idea of one or more tumor suppressor genes on this chromosome arm.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…On the other hand, frequencies of primary OSCC cases, in which down-regulation of miR-137 and miR-193a expression was consistent with tumorspecific hypermethylation around these genes, were relatively high, similar to results in OSCC cell lines. miR-137 is located in chromosomal region 1p21.3, and loss of heterozygosity (LOH) in this region has been reported in meningioma (32), pheochromocytomas (33), and paraganglioma (34). LOH at 17q11.2, where miR-193a is located, has also been described in Barrett's esophageal tumors (35), neurofibromatosis 1 (36), ovarian adenocarcinoma (37), cervical carcinoma (38), and breast cancer (39).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of heterozygosity (LOH) and metaphase/array comparative genomic hybridization (CGH) studies have reported loss of chromosome arms 1p, 3p/q, 11p/q, 17p and 22q as frequent events in pheochromocytomas, indicating the potential presence of tumour suppressor genes on these autosomes. Gain of chromosomal material has appeared less frequently, and the most commonly affected chromosomal regions include 1q, 12q, 17q, 19p/q and 20q (Bender et al 2000, Edstrom et al 2000, August et al 2004, Cascon et al 2005, Jarbo et al 2006, Aarts et al 2006, van Nederveen et al 2009). Here, we have used a high-resolution whole-genome tiling array, consisting of more than 32 000 BAC (bacterial artificial chromosome) clones (32K array), to comprehensively characterize the DNA copy number status of 44 adrenal pheochromocytomas and 9 sympathetic paragangliomas.…”
Section: Introductionmentioning
confidence: 99%